2009
DOI: 10.1556/avet.57.2009.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of energy restriction on thyroid hormone metabolism in chickens

Abstract: Energy restriction induces changes in thyroid hormone economy in the form of a complex adaptation mechanism, in order to conserve energy storage and protein reserves. In the present work, thyroid hormone serum concentrations, hepatic deiodinase enzyme activities and hepatic deiodinase mRNA expression were examined after feed restriction and fasting. We demonstrate that during energy restriction, T 3 concentration is lowered due to a decreased T 4 activation and increased T 3 inactivation. We show that hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…The other report, Gyorffy et al (2009) found that during energy restriction, T 3 concentration is lowered due to a decreased T 4 activation and increased T 3 inactivation. Furthermore, they show that hepatic type-I deiodinase (D1) is not affected by energy restriction, however, hepatic D2 is decreased on both transcriptional and enzyme activity levels.…”
Section: Hormone Thyroid (T 3 and T 4 ) Concentrationsmentioning
confidence: 88%
See 2 more Smart Citations
“…The other report, Gyorffy et al (2009) found that during energy restriction, T 3 concentration is lowered due to a decreased T 4 activation and increased T 3 inactivation. Furthermore, they show that hepatic type-I deiodinase (D1) is not affected by energy restriction, however, hepatic D2 is decreased on both transcriptional and enzyme activity levels.…”
Section: Hormone Thyroid (T 3 and T 4 ) Concentrationsmentioning
confidence: 88%
“…It suggests that degree of feed restrictions applied was not severe because there was a very fast adaptive response with small and transient alterations in T 3 and T 4 concentrations during the period of realimentation. This might be caused by increased activity of the enzyme deiodinase type III (D3) during the realimentation period would recover concentrations of T 3 hormone (Darras et al, 2000;Gyorffy et al, 2009). Furthermore, Gyorffy et al (2009) explained that hypothalamic feedback was not involved in the changes in serum T 3 and T 4 concentrations.…”
Section: Hormone Thyroid (T 3 and T 4 ) Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a decrease in plasma T3 (Fontana et al, 2006) and/or T4 (Gromakova and Konovalenko, 2004) and an increase in rT3 levels are observed (Darras et al, 1995). With respect to peripheral metabolism of TH, fasting has been demonstrated to decrease D2 activity in the liver (Gyorffy et al, 2009), increase D3 activity in this organ (Van der Geyten et al, 1999;Boelen et al, 2012), and to decrease D3 in the kidneys ( Van der Geyten et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Sedangkan pada ayam yang dipelihara pada suhu 32 0 C pemberian antioksidan sari buah mengkudu 1.000 ppm dapat memberikan hasil yang sama dengan kadar tiroksin pada ayam broiler yang dipelihara pada temperatur netral. Aktivitas kalenjar tiroid dipengaruhi oleh kondisi lingkungan, pada ayam yang mengalami cekaman panas aktivitas kelenjar tiroid mengalami penurunan (Sahin et al, 2001;Gyorffy et al, 2009) dan akan mempengaruhi sekresi hormon yang dihasilkannya.…”
Section: Pengaruh Perlakuan Terhadap Kadarunclassified